Generating new knowledge for the field of deaf/hard-of-hearing education: A meta-synthesis of case study research. (2nd January 2019) - Hallenbeck, Taylor; Chouinard, Jill Anne; Enns, Charlotte
ABSTRACT: This meta-synthesis uses descriptive and thematic analysis to explore the use of, and findings from, case study research in the field of Deaf/Hard-of-Hearing (DHH) education. Findings from these analyses provide the field of DHH education with knowledge about how case study has been utilized, ways case study can enrich future research, and descriptions of gaps in the research base. Descriptive analysis findings indicated the case study research approach has been used from 1979 to 2017. Such research has been published primarily in American Annals of the Deaf, utilizes largely interview and observation data collection methods, and is most frequently used for programme evaluation and examination of teacher beliefs and practices. Thematic analysis banded findings from 52 case studies into common themes, identified important considerations for the field, ways case study can enrich the field's use of other research methodologies, and noted gaps in the knowledge base for the education of children and young people who are deaf/hard of hearing.